Prevalence and Risk Factors Associated With Otitis Media with Effusion in Children Visiting Tertiary Care Centre in Malaysia - A, Tikaram; YK, Chew; AB, Zulkiflee; AW, Chong; N, Prepageran (IIUM Medical Journal Malaysia, 2012)
Introduction: The aim of this study is to determine the prevalence of otitis media with effusion (OME) in Malaysian children between three months to twelve years of age and to identify the risk factors associated with it. Materials and methods: This is a cross-sectional study consists of 153 children selected by stratified random sampling method. Parents of these children were interviewed with a structured questionnaire. Clinical examination, including otoscopic examination and tympanometry was performed for each child. Results: The prevalence of OME was 18.3%. There was no statistical significant relationship between OME and gender, race, household size, attendance to daycare center, breast feeding, and exposure to passive smoking, allergy, and asthma. Conclusion: The prevalence of OME is 18.3% in Malaysian children between three months to twelve years of age. Frequency of AOM is a statistically significant factor to the development of OME later in life. The different risk factors associated with OME are still controversial.